Gaps between reflection frameworks and students’ practice: Implications for design education - Ito,A; Taoka,Y; Wan,E; Sadek,M; Mougenot,C; Saito,S (Cambridge University Press, 2024)
This paper aims to identify gaps between the reflection frameworks and students’ practice. Through a systematic literature review (PRISMA) and a qualitative survey of students, 12 reflection frameworks were reviewed, and the 13 challenges students faced at design projects in two design schools were identified. The results indicate three gaps between theory and students’ practice: skills of designers, granularities of reflection items, and supports of bridging reflection to next actions. This study provides insights for future development of support tools to bridge the gaps in design education.